A Simplified Spatial Methodology for Assessing Land Productivity Status in Africa - Barasa, Bernard; Mwanjalolo, Majaliwa J. G.; Banduga, Moses; Katwere, James; Magaya, Paul; Sadadi, Ojoatre; Wanjiru, Lydia; Walusimbi, Margaret N. (Land, 2022)
The degradation of soil, vegetation and socio-economic transformations are a huge threat to Africa’s land production. This study aimed to (i) assess the soil and land productivity of standing biomass and (ii) determine the effect of rainfall on the standing biomass in Eastern Africa. Soil productivity was determined using the Soil Productivity Index (SPI) and a simplified model was developed to estimate the Net Primary Productivity (NPP). The SPI indicators used included soilorganic matter, texture, soil moisture, base-saturation, pH, cation-exchange-capacity, soil-depth and drainage. The inputs of the simplified model are: MODIS Soil Adjusted Vegetation Index (SAVI), soil erosion, soil nutrient content and input, rainfall, land-use/cover and agro-ecological zones. The findings reveal that the countries with the most productive soils are Mauritius, Rwanda and South Sudan—while, for standing biomass, the countries with the highest spatial extent are Mauritius (97%), Rwanda (96%), Uganda (95%), South Sudan (89%), Ethiopia (47%) and Kenya (36%). Standing biomass is dominant in biomes such as natural forests, woodlands, croplands, grasslands, wetlands and tree-plantations. High land productivity was attributed to soil quality and management, land policy reforms, favourable climatic conditions and sustainable land husbandry activities. Rainfall was significantly correlated with standing biomass in most of the studied countries (p < 0.05) except Djibouti and Rwanda. Therefore, monitoring soil health, use and land reforms are key to sustaining vegetative biomass.
Keywords: Land productivity; SAVI; Soil erosion; QGIS; Soil fertility; Africa